Islamic Educational Values in Nussa The Movie Animation - Dedi Novaldi; Satria Nugraha (Universitas Pendidikan Indonesia, 2023)
Film has developed into an educational medium that is considered quite powerful. Filmmakers are required to always not work soberly, but also need to display quality in their films both technically and the material discussed in the film. If not, then filmmakers will drown in the competition. That way it can be ascertained the importance of a quality film with educational value content in it. Nussa is an animated film by the nation's children produced by the production house Visinema Pictures produced in 2021. The film, which won many awards, has kicked off the Indonesian animation film industry to rise from the dominance of foreign animation films in Indonesia. This study aims to determine the Islamic educational values contained in the animated film Nussa. The research was conducted using qualitative research method with content analysis method. The results show that the animated film Nussa contains quite a lot of Islamic educational values that researchers group into three points, namely moral values, aqidah and Islamic parenting.